(untitled) (Texas Journal of Engineering and Technology, 2025)
The emergence of textiles in Central Asia dates back to the first Stone Age - the first Neolithic. We can see the stages of the initial formation of costumes and the stages of the history of the population located in the territory of Uzbekistan. The history of the complete formation of Uzbek national clothes in the late 19th and early 20th centuries was covered until the era of sewing on modern sewing machines